Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

A)\(1-2x+x^2\)
\(=\left(1-x\right)^2\)
B)\(4y+4+y^2\)
\(=2^2+4y+y^2\)
\(=\left(2+y\right)^2\)
C)\(\frac{1}{16}+\frac{1}{2}x+x^2\)
\(=\left(\frac{1}{4}\right)^2+\frac{1}{2}x+x^2\)
\(=\left(\frac{1}{4}+x\right)\)
D)\(36x^2+12xy+y^2\)
\(=\left(6x+y\right)^2\)

\(\left(2x-4y\right)^2+2\left(2x-4y\right)+1=\left(2x-4y+1\right)^2\)

\(x^2-x+\frac{1}{4}\)
\(=x^2-2\cdot\frac{1}{2}\cdot x+\left(\frac{1}{2}\right)^2\)
\(=\left(x-\frac{1}{2}\right)^2\)

a/ 9x2-12xy+4y2 = (3x - 2y)2
b/ 25x2-10x+1 = (5x - 1)2
c/ 9x2-12x+4 = (3x - 2)2
d/ 4x2+20x+25 = (2x + 5)2
e/ x4-4x2+4 = (x2 - 2)2

\(a,x^2+5x+\frac{25}{4}\)
\(=x^2+2.x.\frac{5}{2}+\left(\frac{5}{2}\right)^2\)
\(=\left(x+\frac{5}{2}\right)^2\)

\(4x^2-\frac{1}{9}\left(y+1\right)^2=\left(2x\right)^2-\left(\frac{1}{3}\left(y+1\right)\right)^2\)
\(=\left(2x-\frac{1}{3}\left(y+1\right)\right)\left(2x+\frac{1}{3}\left(y+1\right)\right)\)
\(=\left(2x-\frac{1}{3}y-\frac{1}{3}\right)\left(2x+\frac{1}{3}y+\frac{1}{3}\right)\)

\(a.=\left(2x\right)^2-2.2x.2y+\left(2y\right)^2=\left(2x-2y\right)^2\)
\(b.=\left(3x\right)^2-2.3x.2+2^2=\left(3x-2\right)^2\)
a. 4x2+4y2-8xy=(2x)2+(2y)2-8xy
=(2x-2y)2
b.9x2-12x+4=(3x)2-12x+22
=(3x-2)2
c.xy2+1/4x2y4+1=xy2+(1/2xy2)2+1
=(1/2xy2+2)2

\(1,\\ a,=\left(x+2\right)\left(x^2-2x+4\right)\\ b,=\left(x-4\right)\left(x^2+8x+16\right)\\ c,=\left(3x+1\right)\left(9x^2-3x+1\right)\\ d,=\left(4m-3\right)\left(16m^2+12m+9\right)\\ 2,\\ a,=x^3+125\\ b,=1-x^3\\ c,=y^3+27t^3\)
a)
\(=\left(x+2\right)\left(x^2-2x+4\right)\)
b)
\(=\left(x-4\right)\left(x^2+4x+16\right)\)
c)=\(\left(3x+1\right)\left(9x^2-3x+1\right)\)
d)
=\(\left(4m-3\right)\left(16m^2+12m+9\right)\)
\(4y^2-20y+25\)
\(=\left(2y\right)^2-2.2y.5+5^2\)
\(=\left(2y-5\right)^2\)